Effects of bispectral index monitoring as an adjunct to nurse-administered propofol combined sedation during colonoscopy: a randomized clinical trial - Heo, Jun (Korean J Intern Med, 2016)
BACKGROUND/AIMS: The efficacy of bispectral index (BIS) monitoring during colonoscopic sedation is debated. We aimed to determine whether BIS monitoring was useful for propofol dose titration, and to evaluate differences in sedative administration between expert and inexperienced medical personnel during colonoscopy procedures that required moderate sedation. METHODS: Between February 2012 and August 2013, 280 consecutive patients scheduled to undergo a screening colonoscopy participated in this study and were randomly allocated to the expert or inexperienced endoscopist group. Each group was further divided into either a BIS or a modified Observer’s Assessment of Alertness/Sedation Scale (MOAA/S) subgroup. Trained nurses administered combined propofol sedation and monitored sedation using either the BIS or MOAA/S scale. RESULTS: The mean BIS value throughout the procedure was 74.3 ± 6.7 for all 141 patients in the BIS group. The mean total propofol dose administered in the BIS group was higher than that in the MOAA/S group, independently of the endoscopists’ experience level (36.9 ± 29.6 and 11.3 ± 20.7, respectively; p < 0.001). The total dose of propofol administered was not significantly different between the inexperienced endoscopist group and the expert endoscopist group, both with and without the use of BIS (p = 0.430 and p = 0.640, respectively). CONCLUSIONS: Compared with monitoring using the MOAA/S score alone, BIS monitoring was not effective for titrating the dose of propofol during colonoscopy, irrespective of colonoscopist experience.